Integrated Profiling Identifies PLOD3 as a Potential Prognostic and Immunotherapy Relevant Biomarker in Colorectal Cancer - Shi, Junhong; Bao, Meiyu; Wang, Weifeng; Wu, Xuan; Li, Yueying; Zhao, Changdong; Liu, Weiwei (Frontiers in Immunology, 2021)
Procollagen-Lysine,2-Oxoglutarate 5-Dioxygenase 3 (PLOD3) is related to a variety of human diseases. However, its function in Colorectal cancer (CRC) remains uncertain. PLOD3 expression was analyzed using The Cancer Genome Atlas (TCGA) pan-cancer data. DAVID was used for enrichment analysis of PLOD3-related genes. The correlation between PLOD3 expression and immune cell infiltration was evaluated. Four expression profile datasets (GSE17536, GSE39582, GSE74602, and GSE113513) from Gene Expression Omnibus, and two proteomic datasets were used as validation cohorts for assessing the diagnostic and prognostic value of PLOD3 in CRC. What’s more, we performed immunohistochemistry (IHC) staining for PLOD3 in 160 paired CRC specimens and corresponding adjacent non-tumor tissues. PLOD3 was highly expressed in many tumors including CRC. PLOD3 was upregulated in advanced stage CRCs, and high PLOD3 expression was associated with poor survival. High PLOD3 expression was associated with low levels of B cells, CD4+ T cells, M1 macrophages, CD8+ T cells, and multiple immunerelated characteristics. In addition, the high PLOD3 expression group had a higher TIDE score and a lower tumor mutation burden and microsatellite instability, indicating that patients with high PLOD3 expression may be resistant to immunotherapy. Additional datasets and IHC analysis were used to validate the diagnostic and prognostic value of PLOD3 at the mRNA and protein levels in CRC. Patients with non-response to immunotherapy showed increased PLOD3 expression in an immunotherapy treated dataset. PLOD3 is a potential biomarker for CRC diagnosis and prognosis prediction. CRCs with high PLOD3 expression may be resistant to immune checkpoint therapy.